Paper Stones Revisited: Class Voting, Unionization and the Electoral Decline of the Mainstream Left. Issue 1 (12th March 2021) - Rennwald, Line; Pontusson, Jonas
Abstract : Relying on post-election surveys, we analyze how class and union membership condition voters' abandonment of mainstream Left parties and the alternatives chosen by former mainstream-Left voters in the period 2001–2015. Inspired by Przeworski and Sprague's Paper Stones (1986), our analysis shows that Left parties face a trade-off between mobilizing workers and other voters and that unionization renders workers more loyal to Left parties that mobilize non-workers. By contrast, unionization does not render non-workers more loyal to Left parties that mobilize workers. Union membership increases the likelihood that workers who abandon the mainstream Left continue to vote. It also increases the likelihood that voters abandon the mainstream Left in favor of radical Left parties rather than Center-Right parties. Finally, we show that workers are more likely to abandon mainstream Left parties in favor of radical Right parties than non-workers and that union membership does not affect their propensity to do so. We conclude that reversing the decline of working-class organization should be a long-term objective of mainstream Left parties.